2015
DOI: 10.1021/nl5044067
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Nanojet Array for Fast Detection of Single Nanoparticles in a Flow

Abstract: ABSTRACT:We detect by optical microscopy Au and fluorescent nanoparticles (NPs) during their motion in water-based medium, using an array of dielectric microspheres that are patterned in a microwell array template. The microspheres act as lenses focusing the light originating from a microscope objective into so-called photonic nanojets that expose the medium within a microfluidic channel.When a NP is randomly transported through a nanojet, its back-scattered light (for a bare Au NP) or its fluorescent emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 22 publications
(55 reference statements)
0
54
0
Order By: Relevance
“…For example, Yang et al demonstrated a microfluidic device with an integrated microsphere-lens-array, as shown in Fig. 20(a-c) [98]. The microspheres are patterned in a microwell array template, acting as lenses focusing the light originating from a microscope objective into photonic nanojets that expose the medium within a microfluidic channel.…”
Section: Devices With Integrated Microsphere Superlensmentioning
confidence: 99%
“…For example, Yang et al demonstrated a microfluidic device with an integrated microsphere-lens-array, as shown in Fig. 20(a-c) [98]. The microspheres are patterned in a microwell array template, acting as lenses focusing the light originating from a microscope objective into photonic nanojets that expose the medium within a microfluidic channel.…”
Section: Devices With Integrated Microsphere Superlensmentioning
confidence: 99%
“…The produced parallel photonic nanojets can be used to trap cells with high throughput and high selectivity. Interestingly, researchers found they can also help enhance the backscattering, fluorescence and Raman signal [83][84][85]. The strong confinement of trapping/ excitation field provides new opportunities for trapping and in situ characterization of particles.…”
Section: Fots With Spherical Lensed Tipsmentioning
confidence: 99%
“…Therefore the selection of the proper shape of microstructure depends on the field of various applications. Photonic nanojet is having wide range of applications such as imaging (microscopy [18,19] and Raman spectroscopy [20]), optical tweezing [21], micro etching [22], detection and sensing [23][24][25], laser surgery [17], optical data storage and switching [26,27] etc..…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations are mainly employed to know the behavior of change in light due to the desired structure. There are several methods employed to compute the solution of electromagnetic waves propagated from a finite structure such as transfer matrix method (TMM) [28], plane wave expansion (PWE) method [29], finite element method (FEM) [30], Boundary element method (BEM) [31], multiple multipole method (MMP) [7,8], finite difference time domain (FDTD) method [1][2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] etc. Though there are several methods adopted for computation purpose, however FDTD method is frequently used because of user friendly simulation packages available in the market and to avoid empirical calculations [32].…”
Section: Introductionmentioning
confidence: 99%